Development of a sorption-cooled continuous miniature dilution refrigerator for 100 mK detector testing - May, A; Azzoni, S; Banys, D; Coppi, G; Haynes, V; McCulloch, MA; Melhuish, SJ; Piccirillo, L; Wenninger, J (IOP Publishing, 2019)
As the forthcoming generation of Cosmic Microwave Background observatories move towards the use of large format detector arrays operating at ~100 mK, the need for test cryostats capable of operating in this temperature regime is becoming more pronounced. This has strongly driven the development of several related systems, including the continuous miniature dilution refrigerator (MDR) reported here. The MDR is comprised of a thermally separated mixing chamber, step heat exchangers, twin stills and twin condensation pumps. The pumps are alternately cooled to ~300 mK by a pair of single-shot 1He sorption coolers (cycled in anti-phase) to circulate 3He in the system. The system is therefore closed-cycle, with the circulation of 3He, both in the MDR and sorption coolers, contained to the cold stage. As a result, the reliability of the system is improved through a mechanically simple design and the absence of external connections, gas handling systems, and cold o-rings.